2000
DOI: 10.1144/gsl.sp.2000.181.01.16
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Quaternary vertebrates to palaeoenvironmental and palaeoclimatological reconstructions in Sicily

Abstract: In Sicily few studies have been devoted to the climatic-environmental changes of the Pleistocene and Holocene period. Most of the studies on Quaternary vertebrates in Sicily have been focused on the evolutionary-taxonomic aspects of the fauna. Sicily experienced at least four vertebrate dispersal events during Quaternary time, which are of different provenence (African and/or European) and have been controlled by filtering barriers of different intensities. The marked endemism and the extremely low diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…670,000 to 200,000 ybp. This was also noted by Hutterer et al (1998) It is possible that this species will be referred to Titanochelon on the basis of the coeval and more informative remains of giant tortoises from Alcamo, Sicily (Bonfiglio et al 1999), that likely belong to this genus (Delfino, unpubl. data Hirsch and López-Jurado (1987) of fossil eggs of this presumed species (prior to its description) had concluded that it occurred in the Late Pliocene, between 4,500,00 and 3,500,000 ybp, as also further documented by Hutterer et al (1998).…”
Section: Aldabrachelys Grandidierisupporting
confidence: 52%
“…670,000 to 200,000 ybp. This was also noted by Hutterer et al (1998) It is possible that this species will be referred to Titanochelon on the basis of the coeval and more informative remains of giant tortoises from Alcamo, Sicily (Bonfiglio et al 1999), that likely belong to this genus (Delfino, unpubl. data Hirsch and López-Jurado (1987) of fossil eggs of this presumed species (prior to its description) had concluded that it occurred in the Late Pliocene, between 4,500,00 and 3,500,000 ybp, as also further documented by Hutterer et al (1998).…”
Section: Aldabrachelys Grandidierisupporting
confidence: 52%
“…It is still not known whether Sicily had connections with North Africa during the Middle Pleistocene (Agnesi et al, 1998;Bon glio et al, 1999) and, therefore, whether the origin of the Elephas falconeri F. C. of the "siculo-maltese" archipelago is, at least partially, connected with northward dispersals of African elements. However, it has to be underlined that the giant tortoises discovered in two areas of Sicily (Testudininei indet.…”
Section: Discussionmentioning
confidence: 99%
“…4). Between the Late Glacial and the Holocene climatic optimum Glis and Arvicola disperse on the island, the latter becoming soon extinct during the climatic deterioration that follows the Holocene's climatic optimum (Agnesi et al, 2000;Bonfiglio et al, 2000;Masini et al, 2002a). The dormouse, in contrast, becomes a resident taxa.…”
Section: Late Miocene-pleistocene Populations Of Sicilian Insular Commentioning
confidence: 99%